Líquido cerebroespinhal de cães com doenças do sistema nervoso central - Polidoro Neto, Dakir Nilton (2016)
A retrospective study including the analysis of the cerebrospinal fluid (CSF) of dogs neurologically affected was conducted by the Neurology Service (NS) of the Veterinary Teaching Hospital (VTH) at the Federal University of Santa Maria (FUSM), between 2004 and 2015. The aim of this study was to analyze the results of the CSF of dogs with neurological signs, and compare the changes found in the CSF in two sampling sites in the same patient and see if this test helped the clinician to strengthen clinical suspicion of the major diseases of the central nervous system. Of the 507 patients that underwent CSF analysis, only the analysis of 144 (26.5%) dogs were suited to inclusion criteria. The main diagnosed neurological diseases were distemper (21.6% [n=31]), intervertebral disc disease (IVDD) (52.7% [n=76]), intracranial (IC) tumors (13.2% [n=19]) and tumors which affected the spinal cord (SC) (8.3% [n=12]). Lymphocytic pleocytosis was present in 78.3% (29/37) of samples from dogs with canine distemper and in 23.2% (10/43) of samples from dogs with IVDD. The albuminocytologic dissociation was found in 73% (19/26) of samples from dogs with IC tumors and in 64.3% (9/14) of the samples from dogs with tumors involving the SC. For dogs affected by IVDD, there was statistical significance (p <0.05) between the degree of neurological dysfunction and the total nucleated cells (TNC) and total protein (TP). In 29 dogs, CSF was collected from both the cistern magna (CM) and the lumbar cistern (CL) and in 12 (41.4%) the results were different between the samples of the same dog, where two cases (6, 9%) showed alterations in the sample collected cranial to the injury. It can be concluded that the lymphocytic pleocytosis was the main alteration found in the CSF of dogs with distemper and IVDD and albuminocytologic dissociation in tumors, intracranial and affecting the spinal cord. Dogs affected by IVDD had more severe neurological signs as TNC and TP increased and the CSF was altered even collected cranial to the lesion site and helped the clinician to strengthen the clinical suspicion., but not confirm, the major neurological diseases in dogs.